Diagnosis and Treatment of a Symptomatic Posterior Cruciate Ganglion Cyst in a Child with Autism - Valerio Andreozzi; Edoardo Monaco; Fabio Conteduca; Raffaele Iorio; Daniele Mazza; Piergiorgio Drogo; Andrea Ferretti (Case Reports in Orthopedics)
Introduction. Intra-articular ganglion cysts of the knee joint are rare and mostly incidental findings in magnetic resonance imaging (MRI) or arthroscopy. Posterior cruciate ligament (PCL) ganglion cyst in a child is an extremely rare finding, and to the best of our knowledge, only one case has been described in the literature. We report a case of a large intra-articular ganglion cyst of the knee arising from the PCL in an autistic child. Case Presentation. An 8-year-old Caucasian boy affected by autism presented with nontraumatic knee pain. His parents, observing child’s gait, reported recurrent limp while walking, sometimes accompanied by knee locking. Clinical examination was hindered by the noncompliance of the patient and revealed painful limitation of terminal flexion and extension. MRI scans showed a large ganglion cyst located in the intercondylar notch. Arthroscopy confirmed an intrasubstance PCL ganglion cyst, extending both anteriorly and posteriorly. Complete excision of the cyst was performed, with full recovery of the child and no recurrence. Conclusion. In pediatric patients with pain or limited knee range of motion, physicians should consider the possibility of a ganglion cyst arising from the PCL, despite its rarity. Arthroscopic excision is a safe and effective procedure that guarantees a complete recovery of the patient with the lowest rate of recurrence.